The soft X‐ray and XUV split‐and‐delay unit at beamlines FL23/24 at FLASH2. (15th February 2023) - Dreimann, Matthias; Wahlert, Frank; Eckermann, Dennis; Rosenthal, Felix; Roling, Sebastian; Reiker, Tobias; Kuhlmann, Marion; Toleikis, Sven; Brachmanski, Maciej; Treusch, Rolf; Plönjes, Elke; Siemer, Björn; et al.
Abstract : The properties of the recently installed split‐and‐delay unit at beamlines FL23 and FL24 at FLASH2 are presented. Its operational range, performance parameters and results of a first experiment are described. Abstract : A split‐and‐delay unit for the extreme ultraviolet and soft X‐ray spectral regions has been built which enables time‐resolved experiments at beamlines FL23 and FL24 at the Free‐electron LASer in Hamburg (FLASH). Geometric wavefront splitting at a sharp edge of a beam splitting mirror is applied to split the incoming soft X‐ray pulse into two beams. Ni and Pt coatings at grazing incidence angles have been chosen in order to cover the whole spectral range of FLASH2 and beyond, up to h ν = 1800 eV. In the variable beam path with a grazing incidence angle of ϑd = 1.8°, the total transmission ( T ) ranges are of the order of 0.48 < T < 0.84 for h ν < 100 eV and T > 0.50 for 100 eV < h ν < 650 eV with the Ni coating, and T > 0.06 for h ν < 1800 eV for the Pt coating. For a fixed beam path with a grazing incidence angle of ϑf = 1.3°, a transmission of T > 0.61 with the Ni coating and T > 0.23 with a Pt coating is achieved. Soft X‐ray pump/soft X‐ray probe experiments are possible within a delay range of −5 ps < Δ t < +18 ps with a nominal time resolution of t r = 66 as and a measured timing jitter of t j = 121 ± 2 as. First experiments with the split‐and‐delay unit determined the averaged coherence time of FLASH2 to be τc = 1.75 fs at λ = 8 nm, measured at a purposely reduced coherence of the free‐electron laser.